THE VILLAGE HEAD ELECTION CONFLICT RESOLUTION IN MORAMO COMMUNITY IN MAQÂSHID SYARÎ‘AH PERSPECTIVE - St Halimang, St Halimang (Journal of Contemporary Islam and Muslim Societies, 2020)
Abstract: This article examines the phenomena of social conflict and conflict resolution that accompany the election of village head in Moramo Sub-district, South Konawe, from the perspective of maqâshid syarî‘ah. In order to help to explain the dynamics of social conflict that occurs, the focus of the study was analyzed using two approaches, namely the sociological and theological-normative (syar‘i) approaches which are empirical in nature. Data were collected using participant observation and in-depth interviews, while data analysis used was the interactive model of Miles, Huberman and Saldana. This article concludes that the social conflict in the village head election occurred as an implication of three triggering factors, namely financial factors, camp conflict, and candidate egoism. These triggering backgrounds emerged social segregation and disharmony which resulted in the form of conflict resolution which the local community termed as Putabo. In the perspective of maqâshid syarî‘ah, Putabo is seen as an effort to create benefit which means a form of harmony and conformity between religious principles and the social-social dynamics in Moramo. Keywords: maqâshid syarî‘ah, conflict resolution, putabo